Speciation of lead in soils and relation with its concentration in fruits - Yaman, M; Dilgin, Y; Gucer, S (Elsevier Science Bv, 2000)
The lead concentrations of the fruit samples were determined by using slotted tube atom trap (STAT)-enrichment-flame and graphite furnace atomic absorption spectrometry (FAAS and GF-AAS). The soil samples related to these fruits were also analysed for Pb after extraction with various chemical reagents. The relation between the fruit-lead and soil-extractable lead concentrations was examined in order to explain the bioavailability of lead. A linear relation was observed between the hot Na(2)EDTA extraction-soluble Pb contents in the soil and the Pb concentrations in the mulberry (R-2=0.95), strawberry and apple grown on these soils. Probable chemical forms of lead in soil were evaluated. Acceptable agreement (at least 91%) was achieved between the results of STAT-enrichment-FAAS and GF-AAS. (C) 2000 Elsevier Science B.V. All rights reserved.
Keywords: speciation; lead; soil; fruit; AAS